Fostering Self-Regulated Learning through Character-Integrated Inquiry Laboratory Learning in Basic Elementary Physics - Yusmanila Yusmanila; Ahmad Syarkowi; Desy Eka Muliani; Yeni Nurpatri; Zaturrahmi Zaturrahmi; Sheila Fitriana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines the contribution of character-integrated inquiry-based laboratory learning to enhancing Self-Regulated Learning (SRL) in the Basic Concepts of Elementary Physics course. A descriptive quantitative approach with a posttest-only design was employed. The participants consisted of 68 second-semester students enrolled in the Primary School Teacher Education Program (PGSD) at Universitas Adzkia, including 53 female and 15 male students. All participants were taking the Basic Concepts of Elementary Physics course, which involves laboratory-based inquiry activities. The sample was selected using purposive sampling from two classes with similar academic characteristics.Data were collected using a validated Likert-scale questionnaire measuring key SRL dimensions, including planning, self-monitoring, self-control, reflection, intrinsic motivation, self-efficacy, independence, and responsibility. Data were analyzed using descriptive statistics, including mean scores and percentage distributions.The findings indicate that students demonstrated consistently high levels across all SRL indicators following the implementation of character-integrated inquiry-based laboratory learning. The integration of character values such as responsibility, independence, honesty, perseverance, and curiosity strengthened students’ cognitive, motivational, and behavioral regulation. These results suggest that embedding character values within inquiry-based laboratory learning provides a holistic instructional approach that supports both self-regulation and professional development. Keywords: self-regulated learning, inquiry-based laboratory, character integration, pre-service elementary teachers, basic concepts of elementary physics